Why kids kill inside the minds of school shooters - Langman, Peter F. (Palgrave Macmillan, 2009)
In the ten years since the school massacre at Columbine High School in Colorado, school shootings have become an alarming epidemic. While sociologists have attributed the trigger of violence to peer pressure, such as bullying and social isolation, prominent psychologist Peter Langman argues here that psychological causes are responsible. Drawing on 20 years of clinical experience, Langman offers surprising reasons for why some teens become violent. He divides shooters into three categories, and discusses the role of personality, trauma, and psychosis among school shooters. From examining the material evidence of notorious school shooters at Columbine and Virginia Tech to addressing the mental states of the violent youths he treats, Langman shows how to identify early signs of homicide-prone youth and what preventive measures educators, parents and communities can take to protect themselves from the tragedy.--From publisher description.